The Corrosion Resistance of Nickel Electrocomposite Coating Containing BaFe12O19 Particles. (24th February 2013) - Aruna, S. T.; Savitha, G.; Shedthi, Jyothi; William Grips, V. K.
Abstract : Electroplating composite coating is an effective method to prepare composite coating through the codeposition of metallic, nonmetallic, or polymer particles with metal to improve properties such as corrosion resistance, hardness, and wear performance. This paper reports the synthesis of a novel Ni-BaFe12 O19 magnetic nanocomposite coating exhibiting improved corrosion resistance. In the present paper, BaFe12 O19 particles were synthesized by a single-step solution combustion method and characterized for phase, particle size, and morphology. These particles were incorporated in a nickel metal matrix, and the properties of the coatings like nanohardness and corrosion resistance were investigated. The coating microstructure was also studied using field emission scanning electron microscope. A Vickers hardness of 777 HV was exhibited by Ni-BaFe12 O19, and plain Ni coating exhibited a hardness of 517 HV. The Ni-BaFe12 O19 composite coating exhibited improved corrosion resistance compared to plain Ni coating with an i corr value of 0.034 μ A/cm 2 compared to 0.361 μ A/cm 2 for plain Ni. The Ni-BaFe12 O19 coating also exhibited higher charge transfer and polarization resistance compared to plain Ni coating.